Structural and Biochemical Insights Into Two BAHD Acyltransferases (AtSHT and AtSDT) Involved in Phenolamide Biosynthesis - Wang, Chengyuan; Li, Jianxu; Ma, Miaolian; Lin, Zhaozhu; Hu, Wenli; Lin, Wei; Zhang, Peng (Frontiers in Plant Science, 2021)
Phenolamides represent one of the largest classes of plant-specialized secondary metabolites and function in diverse physiological processes, including defense responses and development. The biosynthesis of phenolamides requires BAHD-family acyltransferases, which transfer acyl-groups from different acyl-donors specifically to amines, the acyl-group acceptors. However, the mechanisms of substrate specificity and multisite-acylation of BAHD-family acyltransferases remain poorly understood. In this study, we provide a structural and biochemical analysis of AtSHT and AtSDT, two representative BAHD-family members that catalyze the multisite acylation of spermidine but show different product profiles. By determining the structures of AtSHT and AtSDT and using structure-based mutagenesis, we identified the residues important for substrate recognition in AtSHT and AtSDT and hypothesized that the acyl acceptor spermidine might adopt a free-rotating conformation in AtSHT, which can undergo mono-, di-, or tri-acylation; while the spermidine molecule in AtSDT might adopt a linear conformation, which only allows mono- or di-acylation to take place. In addition, through sequence similarity network (SSN) and structural modelling analysis, we successfully predicted and verified the functions of two uncharacterized Arabidopsis BAHD acyltransferases, OAO95042.1 and NP_190301.2, which use putrescine as the main acyl-acceptor. Our work not only provides an excellent starting point for understanding multisite acylation in BAHD-family enzymes, but also a feasible methodology for predicting possible acyl acceptor specificity of uncharacterized BAHD-family acyltransferases.